Heat transfer analysis of radiator using different shaped nanoparticles water-based ternary hybrid nanofluid with applications: A fractional model - Arif, Muhammad; Kumam, Poom; Kumam, Wiyada; Mostafa, Zaydan (Case studies in thermal engineering, 2022)
The suspension of nanoparticles in the conventional base fluids getting more attention of the scholars and researchers due to its unique thermal performance in different field of engineering sciences. Nanofluid performed well and showed satisfactory results in the heat transport phenomena which attracted the scientists to suspend different combinations of nanoparticles which named as “hybrid nanofluid”. From the experimental investigations it is found that the rate of heat transfer is higher for hybrid nanofluid as compared to unitary nanofluid. Based on the above motivation the present study is focused to consider water-based ternary hybrid nanofluid with three different shaped nanoparticles i.e, spherical shaped aluminum oxide (Al2O3), cylindrical carbon nanotubes (CNT), and platelet shaped (Graphene) for the advance cooling process of radiator. From the present analysis it is found that this advance water-based ternary hybrid nanofluid showed promising enhancement in the heat transfer rate as compared to hybrid and unitary nanofluid. The present problem is formulated in the form of momentum and energy equations in terms of partial differential equations along with physical initial and boundary conditions. Furthermore, we have considered water-based ternary hybrid nanofluid with different shaped nanoparticles in channel. For the exact solutions the Laplace and Fourier transforms are applied. The influence of all the flow parameters is highlighted using the computational software MATHCAD. Using water-based ternary hybrid nanofluid enhances the rate of heat transfer up-to 33.67% which shows a promising thermal performance in the heat transfer rate. Furthermore, we have used nanoparticles in different ratios and found some interesting results which can be applied in different engineering problems specially, in cooling process.